Giant adrenal myelolipoma: A case report - Gurung, P; Joshi, MR; Hirachand, S; Lakhey, M (Journal of Kathmandu Medical College, 2014)
Adrenal myelolipomas are rare benign tumors. Most are detected incidentally on imaging for non adrenal relatedsymptoms. We report a case of a 78 year old female who presented with non- specifi c complaint of itching all over the bodyand a palpable abdominal mass. CT scan abdomen revealed a large right-sided retroperitoneal mass with thin capsulemeasuring 20.8x15.4x12.7cm. Differential diagnoses considered were retroperitoneal liposarcoma, retroperitonealteratoma and retroperitoneal myelolipoma. The tumor was resected and sent for histopathological examination.Microscopic examination revealed mature adipocytes, islands of hematopoietic tissue and compressed adrenal tissue atthe periphery clinching a diagnosis of adrenal myelolipoma.DOI: http://dx.doi.org/10.3126/jkmc.v2i1.10554Journal of Kathmandu Medical College, Vol. 2, No. 1, Issue 3, Jan.-Mar., 2013, Page: 33-35